The Role of E-Wom As A Mediation of The Influence of Price And Location Perception on Consumer Purchase Intention for Hmns Local Perfume Products in Denpasar - I Gede Krisnanda Aryadi; Ida Ayu Iswari Pidada (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study aims to analyze the effect of price perception and location on purchase intention with electronic word of mouth (e‑WOM) as a mediating variable for HMNS perfume consumers in Denpasar. This research uses a quantitative approach with data collected through an online questionnaire distributed to 162 respondents. Data analysis was conducted using Structural Equation Modeling based on Partial Least Square (SEM‑PLS). The results show that price perception and location have a positive and significant effect on e‑WOM. Furthermore, e‑WOM has a positive and significant effect on purchase intention. Mediation analysis indicates that e‑WOM mediates the relationship between price perception and purchase intention. These findings suggest that appropriate pricing strategies and accessible locations can encourage positive digital communication among consumers and increase purchase intention toward HMNS perfume products